Improved constraints on seismic source parameters of the 2011 Tohoku earthquake from GRACE gravity and gravity gradient changes. Issue 6 (19th March 2014) - Dai, Chunli; Shum, C. K.; Wang, Rongjiang; Wang, Lei; Guo, Junyi; Shang, Kun; Tapley, Byron
Abstract A new approach of using only the north component of gravity change from Gravity Recovery and Climate Experiment (GRACE) data reveals that a substantially higher spatial resolution of the observed seismic deformation following the 2011 Tohoku earthquake is achievable at 333 km or longer. Here we show that GRACE‐observed north component of gravity change, −17.6 ± 1.1 μGal, and the corresponding gravity gradient change, e.g., Txz at 1.25 ± 0.09 mEötvös, agree well with seismic/GPS model predictions. Localized Slepian spectrum analysis further confirms that the GRACE gravity and gravity gradient changes agree well with seismic model spectra and have powers up to the limit of the GRACE solution complete to spherical harmonic degree 60. Using the gravity observations for the fault parameter inversion via simulated annealing algorithm, we show that the estimated slip orientation and centroid location are different from GPS/seismic solutions and potentially due to the additional offshore constraint from GRACE data.